2020
DOI: 10.7150/jca.41122
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative plateletcrit is a Prognostic Biomarker for Survival in Patients with Non-Small Cell Lung Cancer

Abstract: Objectives: Several factors associated with the prognosis of patients with NSCLC have been reported in the literature; however, most of these factors cannot be examined preoperatively. In this study, the clinical utility of platelet parameters in patients with NSCLC who underwent curative resection was evaluated. Materials and Methods: A retrospective study on patients with NSCLC who underwent curative resection from July 2006 to September 2016 was conducted. The Cox proportional hazard regression model was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Higher PCT levels were found in papillary thyroid carcinoma patients than in healthy controls and multinodular goiters ( 20 ). In addition, high PCT levels have been associated with a poor prognosis of pancreatic adenocarcinoma and non-small cell lung cancer ( 21 , 22 ). However, studies focusing on the diagnostic significance of PCT are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Higher PCT levels were found in papillary thyroid carcinoma patients than in healthy controls and multinodular goiters ( 20 ). In addition, high PCT levels have been associated with a poor prognosis of pancreatic adenocarcinoma and non-small cell lung cancer ( 21 , 22 ). However, studies focusing on the diagnostic significance of PCT are limited.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the PCT was higher in papillary thyroid carcinoma group than health control and multinodular goiter [22]. In addition, high PCT has been demonstrated to have a relation with a poor prognosis of pancreatic adenocarcinoma and non-small cell lung cancers (NSCLCs) [23,24]. However, studies focused on the diagnostic signi cance of PCT were limited.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 11 full-text articles including 2421 patients with lung cancer were included. 11,15,[22][23][24][25][26][27][28][29][30] Meanwhile, the meta-analysis only included studies of patients with NSCLC (n ¼ 9). The characteristics of the included studies are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies were conducted in China, 8,[24][25][26]29 three studies were conducted in Turkey, 15,22,23 two studies were conducted in Japan, 11,30 and one study was conducted in Korea. 28 A study by Shi et al had two datasets for HRs for patients with adenocarcinoma and squamous cell carcinoma. 24 Similarly, survival outcomes were described for patients with NSCLC in nine studies, patients with small cell lung cancer (SCLC) in one study, and patients with either NSCLC or SCLC in one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation